The attraction of Bung Hatta Grand Forest Park Tourism potential as a green tourism-based ecotourism - Era Triana; Nengah Tela; Wenny Widya Wahyudi (Universitas Negeri Padang, 2021)
In line with the dynamics of its development, tourism has penetrated various terminology such as ecotourism. Ecotourism is an approach to tourism development that seeks to ensure environmental preservation and keep the natural conditions around tourist destinations. Taman Hutan Raya Bung Hatta (The Bung Hatta Grand Forest Park) is a potential area to be developed into more valuable with more quality in ecotourism. However, the problem is that this site lacks attractiveness and regulations regarding environmental conservation and natural resources of flora and fauna as a valuable attraction in Bung Hatta Grand Forest Park. This study aims to assess the potential development of Taman Hutan Raya Bung Hatta in developing its attractiveness as ecotourism based on green tourism. The analysis in this study uses an observational approach and a deductive-descriptive method. The analyzes done in this research are an analysis of the physical condition of the Bung Hatta Grand Forest Park, an analysis of the attractiveness of the Bung Hatta Grand Forest Park, an analysis of the facilities and infrastructure of the Bung Hatta Grand Forest Park, an analysis of the Potential and Problems of the Bung Hatta Grand Forest Park. Those analyses are carried out with the concept of green-based ecotourism. The assessment of Bung Hatta Grand Forest Park attractiveness potential is from the potential for developing a natural museum, developing a natural laboratory as a means of education, providing a trekking area as an effort to integrate with nature and camping in the natural area of ​​the Bung Hatta Grand Forest without destroying nature. All of this is done while maintaining the sustainability and uniqueness of the vegetation in Bung Hatta Grand Forest Park.